Coleridge's Writings
XV, 281 p.
Keywords: 'This is an important and illuminating collection, however, which could only have been assembled by a formidably learned scholar.' - N. Fruman, Choice From Coleridge's vast writings this book assembles excerpts from Coleridge's inquiries into the workings of consciousness and the soul; man's evolution and divergence from animals; the varieties of human weakness and evil and the creation of culture and belief join to suggest an underlying coherence in Coleridge's interdisciplinary thought. The editor has arranged material from an assortment of public and private writings, and has provided linking commentary to the texts and notes. This volume follows John Morrow's volume, the first in the series, On Politics and Society (1990).